2001
DOI: 10.1182/blood.v97.3.669
|View full text |Cite
|
Sign up to set email alerts
|

Circulating factor VIII immune complexes in patients with type 2 acquired hemophilia A and protection from activated protein C–mediated proteolysis

Abstract: Factor VIII (FVIII) inhibitor antibodies are classified into 2 groups according to the kinetic pattern of FVIII inactivation. Type 2 antibodies are more commonly observed in patients with acquired hemophilia A and do not completely inhibit FVIII activity; in most cases, substantial levels of circulating FVIII are detected. Three type 2 autoantibodies from patients who had normal levels of FVIII antigen despite having low levels of FVIII activity were studied. The antibodies reacted exclusively with the light c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
29
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 43 publications
2
29
0
Order By: Relevance
“…The inhibitory effect of the IgG on binding of FVIII to anhydro-APC was comparable to that of anti-FVIII autoantibodies with A3-C1 epitopes. 21 Notably, all of these autoantibodies were found to bind to the same peptides, supporting the view that the APC binding site is located within the defined peptide region 2009 to 2018.The inhibitory effect of VWF on FVIII binding to anhydro-APC was confirmed in the absence of PL. The present findings indicated that VWF and APC binding sites are in close proximity to each other.…”
supporting
confidence: 57%
See 2 more Smart Citations
“…The inhibitory effect of the IgG on binding of FVIII to anhydro-APC was comparable to that of anti-FVIII autoantibodies with A3-C1 epitopes. 21 Notably, all of these autoantibodies were found to bind to the same peptides, supporting the view that the APC binding site is located within the defined peptide region 2009 to 2018.The inhibitory effect of VWF on FVIII binding to anhydro-APC was confirmed in the absence of PL. The present findings indicated that VWF and APC binding sites are in close proximity to each other.…”
supporting
confidence: 57%
“…Analysis of FVIII cleavage by APC was assessed as previously reported. 21 Briefly, anti-FVIII MoAb JR8 (0.2 M) was immobilized on microtiter wells. After blocking the wells with 4% HSA, 10 nM FVIII, incubated with serial dilutions of antipeptide IgG for 1 hour at 37°C, was added to each well, followed by addition of 5 nM APC, 10 M PL vesicles, and 2.5 mM CaCl 2 .…”
Section: Effects Of Antipeptide Igg On Apc-catalyzed Fviii Inactivationmentioning
confidence: 99%
See 1 more Smart Citation
“…However, persistent circulating IgG immune complexes are not uncommon and are found in patients with different types of allergies, 44 and in some patients with acquired hemophilia A. 25 Consistent with our observations, the acquired hemophilia patients in Nogami et al 25 had disproportionally higher levels of FVIII antigen relative to activity, and antibodies that interacted with the APC cleavage site. Furthermore, dog #3 had antibodies that interacted with the LRP and membrane phospholipid binding sites which may inhibit FVIII clearance from the circulation and contribute to the elevated levels of circulating FVIII antigen.…”
Section: Discussionsupporting
confidence: 79%
“…The details outlining the purification of total IgG antibodies 25,26 and screening the peptide library are provided in supplemental Methods, available on the Blood Web site.…”
Section: Purification Of Ig Antibodies and Screening A Cfviii Peptidementioning
confidence: 99%